2012
DOI: 10.1149/2.020202jss
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Carbon Concentration on the Crystalline Phase and Dielectric Constant of Atomic Layer Deposited HfO2Films on Ge Substrate

Abstract: The effect of the carbon concentration on the crystalline phase and dielectric constant (k) of atomic layer deposited HfO 2 films on Ge substrate was investigated. After annealing, the HfO 2 films grown at 200 • C and 280 • C were crystallized to the tetragonal (t) and monoclinic (m) phases, respectively, which was related to the carbon contents within the films and grain boundary energy. To clarify this, the energy difference between a t-and a m-phases ( E tetra ) was calculated by first principles calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…A similar trend was observed for ferroelectric Hf 0.5 Zr 0.5 O 2 thin films and pure HfO 2 films by Kim et al when the deposition temperature decreased from 280 to 200°C [11,12]. Jung et al used computational simulations to show that the free energy difference between the tetragonal and monoclinic phase decreases with increasing C concentration in HfO 2 , suggesting that including C impurity enhances the stability of the metastable tetragonal phase [33]. Kuenneth et al also examined the effect of C concentration on the free energy values of HfO 2 .…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…A similar trend was observed for ferroelectric Hf 0.5 Zr 0.5 O 2 thin films and pure HfO 2 films by Kim et al when the deposition temperature decreased from 280 to 200°C [11,12]. Jung et al used computational simulations to show that the free energy difference between the tetragonal and monoclinic phase decreases with increasing C concentration in HfO 2 , suggesting that including C impurity enhances the stability of the metastable tetragonal phase [33]. Kuenneth et al also examined the effect of C concentration on the free energy values of HfO 2 .…”
Section: Resultssupporting
confidence: 68%
“…However, they reported that the increase in C concentration did not result in the decrease of the free energy difference between the orthorhombic and monoclinic phase [34]. In Kuenneth et al's work, the substitutional C defects were considered, although the C impurities are generally known as interstitial defects in HfO 2 [33,35]. Therefore, the theoretical calculations did not clearly reveal that the C impurities could decrease [12]), HZO is presented the free energy difference between the tetragonal and orthorhombic phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The flat-band voltage (U FB ) values are very low, and one can say that the studied double-gate dielectric stacks are characterized by a very low amount of charge traps. However, taking into account the hysteresis loop magnitude, as well as Q eff and D itmb values presented in Table I, it can be concluded that in the SiO x N y /HfO x layers bulk or/and at the interface, a fair amount of negative charge are induced.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the k values of the two phases are not very different and are also dependent on the crystallographic directions. 17,20,21 Therefore, making the grain size smaller is an efficient method of achieving the higher-k phase, which has been achieved by doping aliovalent cations, adding impurities (carbon or hydrocarbon), 19,20,22 alloying with ZrO 2 (ZrO 2 films generally have much smaller grain sizes than HfO 2 films in ALD and thus tend to be tetragonal, 23 and using templates such as a rutile TiO 2 film. Although the detailed methods for such transformation of HfO 2 to the higher-k phases are diverse, 16,19 they basically rely on the grain size effect (a smaller grain size prefers the higher-k phase) because the surface (or grain boundary) energy of the higher-k phase is lower than that of the monoclinic phase.…”
Section: Introductionmentioning
confidence: 99%